Historical and Cultural Foundations of Philippines-China Relations - See, Teresita (Social Sciences and Development Review, 2015)
This paper explores the theme suggested by the conference convenors – “The Cultural Diplomacy between the Philippines and China” by highlighting lesser known vignettes and stories in the rich cultural legacy that has been imprinted indelibly on the tapestry of Philippine national culture. The paper emphasizes that this rich cultural heritage that has been implanted long before the Europeans and Americans came to the Philippines forms the building blocks and solid foundations of the relationship between China and the Philippines.